3D‐Printed Underwater Super‐Oleophobic Shark Skin toward the Electricity Generation through Low‐Adhesion Sliding of Magnetic Nanofluid Droplets. (23rd June 2021) - Huang, Jianyu; Wang, Qi; Wu, Zhenhua; Ma, Zheng; Yan, Chunze; Shi, Yusheng; Su, Bin
Abstract: Sustainable energy supply by converting mechanical to electric energy is critical for flexible electronic technologies, soft robots, and biomedical applications. The development of magnetoelectric conversion approaches requires new strategies with lightweight, small, and portable features. To address this need, an underwater magnetic nanofluid droplet‐based generator (UMNDG) is designed to convert the mechanical energy of sliding droplets to electricity. The UMNDG consists of four parts: 3D‐printed underwater superoleophobic surface bioinspired by shark skin, oily magnetic nanofluid droplets, bottom coil, and magnetic part. By improving the manufacturing parameters of 3D‐printed shark skin, underwater superoleophobic and low‐adhesion surfaces can be fabricated, allowing for the magnetic nanofluid droplets to slide upon the surfaces freely. When the magnetic nanofluid droplets slide/leave the bottom coil/magnet region, the magnetic flux passes through the coil changes, yielding the generation of electricity. Maxwell simulation is used to study related working mechanism. Finally, a ladder‐type setup consisting of four UMNDGs is assembled in series, enabling to trigger the lighting of a LED bulb by continuous sliding of magnetic nanofluid droplets. Such a setup design may find use in a wide range of applications, from flexible electronic technologies to bio‐inspired materials that interface with magnetic nanofluid systems. Abstract : Inspired by the dramatic low‐adhesion and drag‐reduced capacity of shark skin, an underwater magnetic nanofluid droplet‐based generator is prepared via a simple and efficient 3D printing technology. The sliding of 80 µL magnetic nanofluid droplets can generate 85.2 µV and 1.1 µA peak values at 10° tilting angle.